Assistant Professor of Economics, Department of Business Administration and Management, Kerala University of Fisheries and Ocean Studies, Kochi, Kerala (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Today we live in a world which is be best  described by the VUCA (Vulnerability,  Uncertainty, Complexity and Ambiguity)  factor. In such a world, with growing level of  uncertainties, personal financial planning is  of paramount importance. A comprehensive  financial plan encompassing all the crucial  aspects of personal finance: savings, insurance,  investment, retirement, taxation and estate,  would not only prepare one for ‘rainy days’ but  also ensure fulfillment of various short and long  term financial goals. Moreover, at present times,  with the onset of the novel corona virus, people  around the globe have faced economic insecurity  and liquidity crunch. In order to survive such  difficult times, personal financial planning is not  only a good proposition but has become a basic  requirement. The paper attempts to highlight  the level of financial planning and financial  wellbeing, along with the reasons and challenges  faced by respondents while planning. In addition to this, the researcher attempts to determine  the association between financial planning and  financial wellbeing.
Keywords: VUCA; financial planning; economic insecurity; financial wellbeing etc.